Pembuatan Pemberian Makanan Tambahan dan MP- ASI sebagai Upaya Pencegahan Stunting pada Kader ‘Aisyiyah - Sawitri Dewi; Purwati Purwati; Diah Atmarina Yuliani (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2020)
Growth and development disorders in infants and children under 2 years of age (baduta) are problems that need to be addressed seriously. This age is an important and critical period in the process of child development, both physical and intellectual. Provision of additional food (PMT) especially for vulnerable groups is one of the supplementation strategies in overcoming nutritional problems. Based on the 2014 Total Diet Survey (SDT) data, it is known that more than half of toddlers (55.7%) have energy intake that is less than the recommended Energy Adequacy Rate (AKE). This shows that the fulfillment of nutrition in infants and toddlers is still lacking. The involvement of health workers, cadres and parents in fulfilling nutrition for children under five is very important, therefore it requires sufficient knowledge and skills in menu selection and food processing as PMT and complementary foods. This activity provides skills and knowledge to cadres in making supplementary food and complementary foods according to the needs of toddlers as well as improving the skills of cadres in counseling. The method used was to provide counseling on nutrition for PMT and complementary foods and how to make them. There was an increase in the knowledge and skills of cadres after participating in this activity. The contribution of cadres in the implementation of counseling on PMT and complementary foods can be an initial illustration of the success of the community in an effort to overcome stunting in infants and toddlers.